Factors influencing the uptake of evidence in child health policy-making: results of a survey among 23 European countries - Kinga Zdunek; Denise Alexander; Peter Schröder-Bäck; Michael Rigby; Mitch Blair (BMC, 2021)
Abstract Background The ability to successfully transfer knowledge across international boundaries to improve health across the European Region is dependent on an in-depth understanding of the many factors involved in policy creation. Across countries we can observe various approaches to evidence usage in the policy-making process. This study, which was a part of the Models of Child Health Appraised (MOCHA) project assessing patterns of children's primary care in Europe, focused on how and what kind of evidence is used in child health policy-making processes in European countries and how it is applied to inform policy and practice. Method In this study, a qualitative approach was used. The data were analysed in accordance with the thematic analysis protocol. The MOCHA project methodology relies on experienced country agents (CA) recruited for the project and paid to deliver child health data in each of 30 European countries. CAs are national experts in the child health field who defined the country-specific structured information and data. A questionnaire designed as a semi-structured survey instrument asked CAs to indicate the sources of evidence used in the policy-making process and what needed to be in place to support evidence uptake in policy and practice. Results In our data we observed two approaches to evidence usage in child health policy formulation. The scientific approach in our understanding refers to the so-called bottom-up initiatives of academia which identify and respond to the population's needs. Institutional approaches can be informed by scientific resources as well; however, the driving forces here are governmental institutions, whose decisions and choices are based not only on the population needs but also on political, economic and organizational factors. The evidence used in Europe can also be of an external or internal nature. Various factors can affect the use of evidence in child health policy-making. Facilitators are correlated with strong scientific culture development, whereas barriers are defined by a poor tradition of implementing changes based on reliable evidence. Conclusions Focusing on the facilitators and actively working to reduce the barriers can perceivably lead to faster and more robust policy-making, including the development of a culture of scientific grounding in policy creation.